2019
DOI: 10.24003/emitter.v7i2.416
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality as Learning Medium for Preservation of Traditional Musical Instruments in Bangka

Abstract: Nowadays the use of technology is something that can be found anywhere. This condition has an impact on the loss of awareness of the Indonesian cultural treasures value in the form of traditional tools. No exception to traditional musical instruments on Bangka Island which began to lose its popularity. At present, most teenagers on Bangka Island cannot play traditional musical instruments. Likewise with the children who do not know and not even know their own regional musical instruments. With the continuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…In the category of other instruments (f=5), only one study is related to the drum kit (Yamabe et al, 2011), while the others are related to traditional instruments from China, Malaysia, and Indonesia. These traditional instruments, which are in danger of being forgotten due to people's preference for modern musical instruments or the higher prices of traditional instruments from East Asia, were introduced to and taught to the younger generation using AR technology to help preserve and promote them (Juniawan & Sylfania, 2019;Permana et al, 2019;Tan & Lim, 2019;Zhang et al, 2015). Furthermore, research was not found on the use of AR technology in voice training or wind instrument training (e.g., flute, clarinet, oboe).…”
Section: Distribution Of the Studies According To The Research Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the category of other instruments (f=5), only one study is related to the drum kit (Yamabe et al, 2011), while the others are related to traditional instruments from China, Malaysia, and Indonesia. These traditional instruments, which are in danger of being forgotten due to people's preference for modern musical instruments or the higher prices of traditional instruments from East Asia, were introduced to and taught to the younger generation using AR technology to help preserve and promote them (Juniawan & Sylfania, 2019;Permana et al, 2019;Tan & Lim, 2019;Zhang et al, 2015). Furthermore, research was not found on the use of AR technology in voice training or wind instrument training (e.g., flute, clarinet, oboe).…”
Section: Distribution Of the Studies According To The Research Subjectsmentioning
confidence: 99%
“…In this study, it was found that this type of research model was used in only one study on early childhood music education (Preka & Rangoussi, 2019). On the other hand, in user experience studies (f=15), a prototype was developed and presented to users for their experience, and their opinions were stated in the results of the study (Berry et al, 2006;Chow et al, 2013;Gomes et al, 2015;Juniawan & Sylfania, 2019;Kerdvibulvech & Saito, 2008;Löchtefeld et al, 2011;Molloy et al, 2019;Motokawa & Saito, 2006;Permana et al, 2019;Raymaekers et al, 2014;Rigby et al, 2020;Rusiñol et al, 2018;Tan & Lim, 2019;Torres & Figueroa, 2018;Yamabe et al, 2011). These studies have not been considered designbased models but have been explained under "user experience."…”
Section: Distribution Of the Studies According To The Research Designmentioning
confidence: 99%
“…Kemasan menjadi faktor penting dalam meningkatkan nilai jual produk, selain itu kemasan berfungsi untuk melindungi produk, media promosi, menjadi identitas suatu produk, memperpanjang umur simpan produk, memudahkan dalam pendistribusian dan pemasaran produk, serta memenuhi kebutuhan dan kepuasan konsumen (Muryeti et al, 2018). Kemasan yang unik dan menarik meningkatkan daya minat beli oleh pembeli (Juniawan & Sylfania, 2019). Selain, pemilihan kemasan dan material kemasan akan mempengaruhi kualitas dan umur simpan (kadaluarsa) dari produk (Ningtyas, 2021) (Satria et al, 2017) UKM Donat Chibi adalah UKM yang berada pada di Kawasan Cipayung.…”
Section: Pendahuluanunclassified
“…AR has been used as for promoting the product of Saran Sejahtera [6], another application is as a medium for introducing Indonesian traditional musical instruments [7] and Bangka Belitung traditional musical instrument [8]- [9], as media to learn The Cirebon Mask Dance [10], as a medium for identifying images of national figures on banknotes [11], as a tourism introduction media with testing results which conclude that all users are happy with the applications [12], as a prop for the human heart. This study uses a 3D technique that can track objects so as to give the effect of a 3D object that can be held in the user's hand.…”
Section: Introductionmentioning
confidence: 99%